Current Transport Mechanisms in Zinc Oxide/Silicon Carbide Heterojunction Light‐Emitting Diodes. Issue 9 (24th June 2020) - Przezdziecka, Ewa; Chusnutdinow, Sergij; Wierzbicka, Aleksandra; Guziewicz, Marek; Prucnal, Sławomir; Stachowicz, Marcin; Zaleszczyk, Wojciech; Zhou, Shengqiang; Kozanecki, Adrian
Abstract : Herein, the properties of ZnO:N/ n ‐SiC heterojunctions (HJs) and light‐emitting diodes based on them are studied. The HJs are grown by molecular beam epitaxy. Active nitrogen generated by a radio frequency plasma source is used for p ‐type doping. The location of the space charge area on the ZnO:N/ n ‐SiC interface is revealed by electron‐beam‐induced current (EBIC) scans. The diffusion lengths of holes and electrons are calculated. This article presents the characterization of ZnO:N/ n ‐SiC HJs and reveals the presence of tunneling‐related current transport in them as well as the contribution of exponentially distributed traps at large voltage bias. Electroluminescence (EL) is measured at ambient pressure by a standard EL system and also at 77 K in vacuum by a system utilizing EBIC in a scanning electron microscope. Analysis of the light output power at higher current level indicates the limited effect of nonradiative defects in this structure. EL results are compared with cathodoluminescence spectra. Color temperature for HJs based on the EL spectra is also calculated. Abstract : The properties of ZnO:N/ n ‐SiC heterojunctions are analyzed by current–voltage and electron‐beam‐induced current (EBIC) measurements. Electroluminescence (EL) is measured at ambient pressure by a standard EL system and in the vacuum by a system utilizing EBIC in a scanning electron microscope. Analysis of the light output power indicates a limited effect of nonradiative defects in this structure.